Le détournement du commissariat : l’exposition chorégraphique chez Boris Charmatz et Xavier Le Roy - Hudon, Véronique (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2018)
Today, it is not unusual to see performing artists present exhibitions in galleries or museums. The French choreographers Boris Charmatz and Xavier Le Roy each revisit the format of the exhibition as a performative site, rather than a space devoted to artistic objects. At the border between curating and artistic practice, their work questions the museum space as a place for the production of knowledge. Through living practice, choreographers redefine the work of art’s modes of production, mediation, and reception, while also reformulating aesthetic experience through the coexistence of bodies, documents, and artistic media in the museum space. By reflecting on the critical potential of Boris Charmatz’s Flip Book exhibitions and Xavier Le Roy’s “Retrospective,” this article seeks to define their curatorial strategies, as well as the political consequences of their engagement in the institution.